2019
DOI: 10.33448/rsd-v8i10.1421
|View full text |Cite
|
Sign up to set email alerts
|

Por trás da tela: uso e consequências dos jogos online para multijogadores

Abstract: An asystematic review of the national and international literature was carried out, in order to reflect on the use and consequences of the use of the MMORPG. Theoretical material was used in the following electronic databases: Scielo, Google Scholar, Pepsic, Scopus, Sciense Direrct, books, theses and dissertations of CAPES, with the following descriptors "videogame", "MMORPG", "online gaming" gaming disorder "," internet "," behavioral addiction ", without delimitation of year of publication, in the English, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, NSSI is a risk factor for future suicide (American Psychiatric Association, 2013;Lim et al, 2019). Communication on NSSI on the Internet has increased in the last years, and the type of contents available for users and their repercussion in the daily life of these individuals is worrying (Lewis, Heath, Michal, & Duggan, 2012;Marchant et al, 2017;Cassel;Terribile;Machado, 2019). A review study identified that the Internet could catalyze a support network for people with NSSI, but it also promotes access to NSSI media, content that normalizes this behavior, violent content, intimidation or harassment of vulnerable people (Moreno et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NSSI is a risk factor for future suicide (American Psychiatric Association, 2013;Lim et al, 2019). Communication on NSSI on the Internet has increased in the last years, and the type of contents available for users and their repercussion in the daily life of these individuals is worrying (Lewis, Heath, Michal, & Duggan, 2012;Marchant et al, 2017;Cassel;Terribile;Machado, 2019). A review study identified that the Internet could catalyze a support network for people with NSSI, but it also promotes access to NSSI media, content that normalizes this behavior, violent content, intimidation or harassment of vulnerable people (Moreno et al, 2016).…”
Section: Introductionmentioning
confidence: 99%